Life Cycle Assessment in Crude Palm Oil Production: Optimization of Oil Extraction Rate - Muhammad Rizky Zen; Agus Adi Putra; Uswatun Mujahidah; Michelle Maria Magdalena Napitupulu; Chairunnisa Noviarini; Muhammad Miftahur Rahman (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2024)
Indonesia, as the foremost producer of palm oil globally, faces crucial environmental challenges. Besides palm oil production plays an important role in economic growth and national development, it also has environmental consequences from the production process. Crude Palm Oil (CPO) Industries face challenges balancing economic growth and environmental sustainability. This research carries out an environmental impact analysis of CPO production with the Life Cycle Assessment method using openLCA software 2.03 with CML-IA Baseline and ReCiPe 2016 Midpoint (H). Scope of this research adopts cradle-to-gate analysis with declaration unit of 1 kg CPO product. In this analysis, it was found that CPO production had a significant impact on GWP, Terrestrial Eco-toxicity Potential, and Land Use Change. So this research also explores the environmental impact of increased Oil Extraction Rate (OER) scenario with an OER of 21% and 22% compared to OER in current production activities. The research showed that all impacts decreased when OER was increased, impacts decreased of around 3% at OER 21% and decreased of around 8% at OER 22%. These findings confirm the potential feasibility of implementation based on increasing OER in the Palm Oil Industry to achieve targets for sustainable improvement.